"An Overview of Indian Higher Education System: During & After Covid-19 Pandemic Period" - Mr. Lalitkumar Premchandra Patil, Dr. Hiresh S. Luhar (PalArch's Journal of Archaeology of Egypt / Egyptology, 2021)
Ongoing Covid-19 pandemic is spread all over the country and abroad. It has an adverse effect on entire education system of the country. Till date we have not been able to get out of this difficult situation and it is uncertain that when the entire world will get out of this situation completely. Almost all educational Institutions are closed all over the country and teaching- learning is being done online. Looking at all of this, it seems that in the coming time, many challenges may have to be faced, but in spite of so many challenges, the higher education Institutes managed very well and continued learning and teaching in a sustained manner. Information technology and internet are proven successful to make education accessible to students. The main purpose of this study is to analyze how education system is being further enhanced by technology. Higher education Institutions in India are providing uninterrupted educational services to learners and a lot of resources are being provided for learning and teaching. New trends, new approaches, new tools & learning technology has come. Further the researchers has discussed that post-Covid-19 how the education can be provided to all students with the system of advanced teaching in India through higher education learning and new methods of teaching (technology). Education / online education will be imparted to all students. Some suggestions have also been made as to how educational activities can be further ameliorated in the event of the Covid-19 pandemic.